Effect of nanofiller incorporation on thermomechanical and toughness of poly (vinyl alcohol)-based electrospun nanofibrous bionanocomposites. (February 2019) - Enayati, Mohammad Saeid; Neisiany, Rasoul Esmaeely; Sajkiewicz, Paweł; Behzad, Tayebeh; Denis, Piotr; Pierini, Filippo
Highlights: Nanohydroxy apatite and cellulose nanofibers were incorporated into electrospun PVA nanofibers. Both nanofillers significantly increased the stiffness of the fibrous nanocomposites. Neat electrospun PVA mats showed ductile fracture whereas by nanofiller incorporation, fracture altered to a brittle mode. Abstract: The current work studies the electrospun poly (vinyl alcohol) (PVA) nanofibers and its nanocomposites including nanohydroxy apatite (nHAp) and nHAp/cellulose nanofibers (CNFs), emphasizing the impact of nanofillers on the toughness of nanofibers. PVA nanofibers were incorporated with 10 wt% of nHAp and then various amounts of CNF were added to subsequent PVA/nHAp fibrous nanocomposites. The morphology of nonwoven mats was studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). While neat PVA nanofibers were smooth and uniform in thickness, the nanofiller loading resulted in thinner fibers with less uniformity. Furthermore, the thermal properties of the nonwoven network of fibers were characterized employing thermogravimetric analysis (TGA). Although the maximum loss mass temperature of PVA was partially reduced upon addition of nanofillers, the onset of decomposition was not altered. The mechanical characterizations were performed using static tensile and dynamic mechanical analysis (DMA). Compared to neat PVA mats, the tensile test of nanocomposites mats demonstrated the significant increase in Young's modulus; however, strain at break was dramatically reduced. In addition, the fracture work was assessed from the area under the stress-strain curve, which showed brittleness of fibrous nanocomposites due to the nanofiller incorporation. Field emission SEM (FE-SEM) was employed to scan the fracture surface of stretched fibers. The increase in modulus of electrospun mats was also shown by DMA in frequency mode. In parallel, both tensile test and DMA confirmed the change in fracture of PVA fibers from a tough to brittle mode, due to the nanofiller addition.